EFFECTIVENESS OF REVENUE MANAGEMENT CONTROL SYSTEMS IN IMPROVING COMPANY PERFORMANCE - Alfonsus Jantong; Lukman Lukman; Gladys Anastasia Faihu (SIMAK, 2023)
The purpose of this study was to determine the effectiveness of the revenue management control system in improving company performance (Case Study at PT. Citra Van Titipan Kilat Makassar Branch). This study uses qualitative methods using interviews and documentation as data collection. The results of this study indicate that PT. Image of Van Custodian Express Makassar Branch has implemented a revenue management control system in this company but its implementation is not satisfactory.